2022
DOI: 10.1371/journal.pgen.1010300
|View full text |Cite
|
Sign up to set email alerts
|

RaScALL: Rapid (Ra) screening (Sc) of RNA-seq data for prognostically significant genomic alterations in acute lymphoblastic leukaemia (ALL)

Abstract: RNA-sequencing (RNA-seq) efforts in acute lymphoblastic leukaemia (ALL) have identified numerous prognostically significant genomic alterations which can guide diagnostic risk stratification and treatment choices when detected early. However, integrating RNA-seq in a clinical setting requires rapid detection and accurate reporting of clinically relevant alterations. Here we present RaScALL, an implementation of the k-mer based variant detection tool km, capable of identifying more than 100 prognostically signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…Diagnostic definitions of molecular BCP‐ALL subtypes 1 , 2 rely primarily on genomic drivers. Gene fusion calling 9 , 40 and identification of driver hotspot variants 5 , 10 from RNA‐Seq data is well established. Recently, it has been shown that virtual karyotypes can also be imputed from RNA‐Seq data 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic definitions of molecular BCP‐ALL subtypes 1 , 2 rely primarily on genomic drivers. Gene fusion calling 9 , 40 and identification of driver hotspot variants 5 , 10 from RNA‐Seq data is well established. Recently, it has been shown that virtual karyotypes can also be imputed from RNA‐Seq data 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Further implementation as routine clinical diagnostic requires unified analysis methods. Calling of driver gene fusions 9 , 10 is well established and novel approaches for the identification of hotspot single‐nucleotide 10 variants and virtual karyoytpes 11 exist. Yet only few approaches for systematic gene expression analysis are currently available 12–14 …”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic analyses were performed on bone marrow samples collected at the time of T‐ALL presentation, as well as first relapse, and analysed using our bioinformatic pipelines for the detection of gene fusions, SNVs, insertion/deletion alterations (INDELs) and assessment of gene expression 8 . mRNA‐Seq identified several non‐synonymous SNVs and INDELs of clinical relevance (Table S1; Figure 1A), which were validated by PCR and Sanger sequencing (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the detection of deletions in the IKZF1 gene in Brown et al, we have tailored an algorithm to specifically look for these novel isoforms in RNA-seq. A recent approach that performs more comprehensive RNA-seq analysis specific to ALL is RasCALL (Rehn et al 2022). Toblerone is not intended to be a comprehensive structural variant detection method however it complements existing RNA-seq analysis tools in cancer such as fusion detection (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The focal deletion results in the production of a dominant-negative isoform, IK6, lacking the N-terminal DNA-binding domains of IKAROS (Mullighan et al 2009;Dörge et al 2013;van der Veer et al 2013). Previously we and others have showed that IK6 could be detected using RNA-seq (Brown et al 2020;Tran et al 2022;Rehn et al 2022). In our work, we did so by adding the deletion transcript to the reference transcriptome and measuring the transcripts per million (TPM) (Brown et al 2020).…”
Section: Introductionmentioning
confidence: 99%